Fiscal Imbalances in Nepal's Federalism : An Empirical Analysis - Wagle, Achyut (NRB Economic Review, 2018)
The most overarching and universally accepted imperative to federalize any unitary nation-state is to reduce, both vertical and horizontal, fiscal imbalances as ensured availability of financial resources only could augment any form of well-being and prosperity. Such imbalances constrict all desirable economic outcomes. But, while carving seven States out of the erstwhile unitary state, any other priority like identity or territoriality may have prevailed but fiscal imbalance. This study shows that mainly vertical fiscal imbalance still alarmingly persists even after federalization of the country. The Panel Corrected Standard Error (PCSE) model examines how these imbalances between the federation and the sub-national units (vertical) and, also among the States themselves(horizontal) are likely to impact on the fiscal federalism framework and its functionality. It contends that highly skewed distribution and mobilization of financial resources essentially defeats the very rationale of federalizing Nepal and, much debated identity consideration in federalism has no positive welfare implication.